2020
DOI: 10.1101/2020.08.14.251645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Somite surface tension buffers imprecise segment lengths to ensure left-right symmetry

Abstract: The body axis of vertebrate embryos is periodically segmented into bilaterally symmetric pairs of somites. The anteroposterior length and boundary position of somites are thought to be molecularly determined prior to somite morphogenesis. We show that in zebrafish embryos, initial somite lengths and positions are imprecise and many somites form left-right asymmetrically. Yet, within an hour, lengths are adjusted, becoming more symmetric, through somite deformations occurring independently on the left and right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…Unexpectedly, we find that discs adjust their volume through a major adjustment step taking place immediately after the L/P transition. This contrasts with recent descriptions made in zebra fish where symmetrically developing inner ears and somites adjust progressively over time 20,21 . We show that the relaxin-like Dilp8 is required for a major adjustment step taking place after WPP.…”
Section: Discussioncontrasting
confidence: 97%
“…Unexpectedly, we find that discs adjust their volume through a major adjustment step taking place immediately after the L/P transition. This contrasts with recent descriptions made in zebra fish where symmetrically developing inner ears and somites adjust progressively over time 20,21 . We show that the relaxin-like Dilp8 is required for a major adjustment step taking place after WPP.…”
Section: Discussioncontrasting
confidence: 97%
“…It is the outstanding optical clarity of the ventro-caudal region of zebrafish embryos as the caudal somites develop that allowed us to identify for the first time the earliest morphological individualization of the sclerotome, as a distinct ventral cell cluster appearing at somite maturation stage S5, before these cells become mesenchymal cells migrating both dorsal- and ventral-wards. Interestingly, Naganathan et al 43 recently found that up to stage S4, somites undergo a mechanical adjustment of their A-P length that is facilitated by somite surface tension, which requires the somite to be fully packed within an uninterrupted basal lamina. It therefore makes sense that cell migrations out of the somite, which require to break the basal lamina, are “ allowed” to begin only once this mechanical rearrangement of the somite has been completed, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that mechanics can help achieve robust somitogenesis was recently put forward in the context of lateral symmetry between somites 28 . Albeit in a different context, our results support the idea that mechanics enables robust somite formation, as the amplitude of tension fluctuations appears to be optimally tuned to enable maximal somite boundary straightening with minimal variation in boundary straightness and minimal somite morphological defects.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanics has long been recognized to play a role in somite morphogenesis 2326 . Previous observations of rounding and spontaneous segmentation of mesodermal explants in chick and quail 27 , as well as the rounding of explanted somite tissue in zebrafish 28 , suggested that tissue surface tension alone may drive segmentation, akin to a Plateau-Rayleigh instability in fluids 29 . However, recent experiments have shown that the PSM tissue is in a solid-like state at the timescales of somite formation 30 , indicating that a different physical mechanism may be at play to shape somites.…”
mentioning
confidence: 97%